The effect of unemployment on socio economic status of the people in jaffna district, Sri lanka - Godwin Phillip, P.M.; Thayaparan, A.; Gnanachandran, G. (University of Jaffna, 2014)
Among the working-age population, one of the most damaging individual experiences is unemployment. Mostly it is a serious issue in third world countries like Sri Lanka. The main aim of this study is to identify the nature of the unemployment and its imp -being among the working age group with respect to their vocational activities such as income, savings housing, health, education and other social welfare in Jaffna District in Sri Lanka. The primary data were collected from 100 unemployed households in Jaffna District by using structured questionnaire. The techniques such as descriptive statistics such as descriptive and regression model were used in this study. The results of the regression model indicate that the unemployment negatively affecting in all economic and social conditions of the people in Jaffna District. Finally the overall results reveal that among unemployed people, non-pecuniary factor such as job prospects, health and social relations show significant effects on individual well-being, along with their income. Policy makers have to take necessary actions incorporating strategic approaches which can reduce the unemployment and improve the well being of the people in Jaffna District, Sri Lanka. Especially government have to consider this main economic problem in its future changes of monetary and fiscal policy.
Keywords: Unemployment; Well-being; Education; Income